2021
DOI: 10.1016/j.arth.2020.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Preparing for an Era of Episode-Based Care in Total Joint Arthroplasty

Abstract: With a history of steadily rising healthcare costs, the United States faces an unprecedented set of health and financial challenges. The COVID-19 pandemic will only exacerbate these challenges, and it is of paramount importance to reform and refine health systems to maximize the value of care delivered to the patient. Recent developments related to value improvement in total joint arthroplasty suggest episode-based payment is likely to become standard practice given the current healthcare environment. Conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Several studies describe patient satisfaction with telehealth programs [ 68 , 69 , 70 , 71 , 72 , 73 ]. Buvik et al [ 74 ] found, in a randomized controlled trial, that 86% of patients having remote consultations preferred a video-assisted consultation for the next visit.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies describe patient satisfaction with telehealth programs [ 68 , 69 , 70 , 71 , 72 , 73 ]. Buvik et al [ 74 ] found, in a randomized controlled trial, that 86% of patients having remote consultations preferred a video-assisted consultation for the next visit.…”
Section: Resultsmentioning
confidence: 99%
“…Although assessing these goals is challenging, PROMs are vital as they present a validated and quantifiable measure of the quality of a patient's subjective health experience. As incentives to understand value are increased with rising health-care costs, value-based repayment programs, and employers directing patients toward "higher-value" surgeons 31 , the need for the standardization of PROM reporting is especially apparent. The American Joint Replacement Registry and other cohorts currently publish hospital-level and site-specific PROM results 32 , and this aggregation of PROMs in clinical data registries will allow for comparison among providers and health-care centers.…”
Section: Overviewmentioning
confidence: 99%
“…Total hip arthroplasty (THA) has been used for over five decades for treating hip osteoarthritis, with the aims of reducing pain levels and ameliorating articular function and quality of life [ 1 ]. Furthermore, it has become widely utilized due to population aging [ 2 ]. Nevertheless, THA is generally considered to be a traumatic surgical procedure and it has been associated with intraoperative blood loss, intense postoperative pain, requirement for intensive care unit (ICU) use, and prolonged immobilization.…”
Section: Introductionmentioning
confidence: 99%